USE OF GNSS SYSTEM AND SGN POINTS IN THE REPUBLIC OF UZBEKISTAN - Kasimov Mahmud (Web of Journals Publishing, 2024)
This article examines the use of Global Navigation Satellite System (GNSS) technologies in Uzbekistan, focusing on their applications in geodesy, land management, and natural disaster monitoring. The study highlights the integration of GNSS systems with the country’s national geodetic network and discusses the advantages of high-precision measurement, including the use of RTK and PPK technologies that provide millimeter-level accuracy. The article also explores the technical challenges such as signal disruption in mountainous areas and the cost of expanding the geodetic infrastructure. Additionally, the article discusses the potential future developments in GNSS technology, including the integration with modern technologies such as drones and smart city initiatives. The findings suggest that while there are challenges, the future of GNSS systems in Uzbekistan is promising, with significant contributions to urban planning, environmental monitoring, and disaster risk management.
Keywords: GNSS, geodesy, Uzbekistan, RTK, PPK, geodetic network, signal disruption, drones, smart cities, land management, environmental monitoring, natural disasters, satellite navigation.